2015
DOI: 10.1007/s12223-015-0418-7
|View full text |Cite
|
Sign up to set email alerts
|

Light-induced inhibition of laccase in Pycnoporus sanguineus

Abstract: The aim was to determine which specific regions of the visible light spectrum were responsible for the induction or inhibition of laccase in Pycnoporus sanguineus. Cultures were exposed to various bandwidth lights: blue (460 nm), green (525 nm), white (a combination of 460 and 560 nm), red (660 nm), and darkness. The results indicate that short wavelengths strongly inhibit the production of laccase: green (3.76 ± 1.12 U/L), blue (1.94 ± 0.36 U/L), and white (1.05 ± 0.21 U/L) in proportions of 85.8, 92.6, and 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
0
8
0
2
Order By: Relevance
“…This species is found in tropical and subtropical areas and is known for its high lignocellulolytic potential, for producing laccase as its main extracellular ligninase (Hernández et al, 2016), and for effectively degrading several classes of dyes (Moreira-Neto et al, 2013). However, laccase production depends on fungal cultivation and growth conditions, and the expression of different laccase isozymes is related to the presence of nutrients and inducers in the cultivation media (Valle et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This species is found in tropical and subtropical areas and is known for its high lignocellulolytic potential, for producing laccase as its main extracellular ligninase (Hernández et al, 2016), and for effectively degrading several classes of dyes (Moreira-Neto et al, 2013). However, laccase production depends on fungal cultivation and growth conditions, and the expression of different laccase isozymes is related to the presence of nutrients and inducers in the cultivation media (Valle et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Laccase activity by Pleurotus eringyii [39] was not significantly affected by the light conditions tested, but light stimulated its aryl-alcohol oxidase activity. On the contrary, Hernández et al [15] found out that short wavelengths (green, blue, and white) strongly inhibited laccase production by Pycnoporus sanguineus whereas maximum activity was induced in darkness. This can be explained as an ecological mechanism of environmental recognition, wood rot fungi develop in darkness inside lignocellulose structures.…”
Section: Discussionmentioning
confidence: 95%
“…For example for copper the real value is the concentration of copper in the medium and is expressed in μM. Measured responses are depicted in columns [14][15][16][17][18][19]. Values represent the mean of three replicates, SEM <5% | 953 transitions and accompanying expression of genes associated with regulation in the production of exoenzymes and with various bioprocesses in fungi such as sporulation, fruit body development, and metabolite production [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pycnoporus sanguineus (L.) Murrill (Polyporaceae) é um fungo de ocorrência tropical e subtropical comum em todo o Brasil. Considerado um FPM, apresenta elevado potencial ligninolí-tico e produz lacase como a principal enzima degradadora de lignina (HERNÁNDEZ et al, 2016).…”
Section: Introductionunclassified